Protocatechuic acid inhibits TGF-β1-induced proliferation and migration of human airway smooth muscle cells - Yu-Dong Liu; Xin Sun; Yao Zhang; Hua-Jie Wu; Hao Wang; Rui Yang (Elsevier, 2019)
Protocatechuic acid (3, 4-dihydroxybenzoic acid, PCA) is a major metabolite of anthocyanins and was reported to possess anti-allergic response. However, the effects of PCA on airway smooth muscle cells (ASMCs) proliferation and migration remain unclear. Therefore, this study aims to investigate the effects of PCA on proliferation and migration of ASMCs. ASMCs were pre-incubated with various concentrations of PCA for 30 min before stimulation with transforming growth factor-β1 (TGF-β1) for different times. Cell proliferation was determined using the colony formation assay. Cell migration was detected using the Transwell chamber assay. The levels of type I collagen, fibronectin, phosphorylated Smad2, Smad2, phosphorylated Smad3 and Smad3 were detected by western blot analysis. Our results demonstrated that PCA inhibited the proliferation and migration of ASMCs, as well as suppressed the expression levels of type I collagen and fibronectin in ASMCs induced by TGF-β1. Furthermore, PCA obviously down-regulated the phosphorylation levels of Smad2/3 in ASMCs exposed to TGF-β1. Taken together, the present results have revealed that PCA inhibits asthma airway remodeling by suppressing proliferation and extracellular matrix (ECM) protein deposition in TGF-β1-mediated ASMCs via the inactivation of Smad2/3 signaling pathway. Therefore, PCA may be useful for the prevention or treatment of asthma airway remodeling. Keywords: Asthma, Protocatechuic acid (PCA), Airway smooth muscle cells (ASMCs), Transforming growth factor-beta1 (TGF-β1)